Fourth Five Year Plan Draft Out-Line Nagaland - Planning Commission (Planning Commission, 1964)
Nagaland came into being on the 1st December, 1963, as a full-fledged State, though as a separate unit of Administration, it was in existence from the 1st December, 1957. The State comprises of an area of 6,366 Sq. miles with a population of 3,69,200 (1961 Census). The density of population is approximately 58 per Sq. mile. Almost 98 per cent of the population are directly or indirectly dependent on Agriculture.
Government of Nagaland, Planning and Co-ordination Department